2001
DOI: 10.1002/jso.1127
|View full text |Cite
|
Sign up to set email alerts
|

Complications and functional evaluation of 17 saddle prostheses for resection of periacetabular tumors*

Abstract: Seventeen saddle prostheses were inserted between 1988 and 1997 after resection of periacetabular tumors. The tumors involved the zones II and III of Enneking classification in 13 patients, the zones I and II in 2 patients, and the zone II in 2 patients. The tumors included 11 chondrosarcomas, 3 Ewing sarcomas, 2 giant cells tumors, and 1 metastasis of renal carcinoma. The tumoral resection was wide "en bloc" in 14 cases, marginal in 2 cases, and intratumoral in 1 case. The mean follow-up period of the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
108
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(129 citation statements)
references
References 24 publications
(44 reference statements)
12
108
0
5
Order By: Relevance
“…The major complication rate in the present and other series is summarized (Table 3). Among the postoperative complications, deep infection was the most serious and frequent complication also in the present series (32%), similar to other reconstructive procedures; the rates of deep infection have been reported as 18% to 33% in saddle prostheses [4,21,25,28], 25% to 30% in custom-made * Thirteen patients were excluded from MSTS/ISOLS functional evaluation because they died of disease at 4-34 months postoperatively, and another one patient was excluded as a result of hindquarter amputation performed for local recurrence of iliac chondrosarcoma after C-THA; MSTS/ISOLS = Musculoskeletal Tumor Society/International Society of Limb Salvage; F = female; M = male; P-F = proximal femur; MFH = malignant fibrous histiocytoma; GCT = giant cell tumor. * Case series with a mean followup period over 60 months are only listed in Table 2; 15 of 17 patients were primarily treated with an allograft-THA prosthesis composite; à primary malignant bone and soft tissue tumors in 82 patients, solitary metastatic bone tumors in seven, plasmacytoma/myeloma in six, and benign bone tumors in three (fibrous dysplasia two, chondroblastoma one); § the cumulative implant survival rate of C-THA was 67% at 5 and 10 years postoperatively, when patients' death was interpreted as censored to calculate cumulative survival rate.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The major complication rate in the present and other series is summarized (Table 3). Among the postoperative complications, deep infection was the most serious and frequent complication also in the present series (32%), similar to other reconstructive procedures; the rates of deep infection have been reported as 18% to 33% in saddle prostheses [4,21,25,28], 25% to 30% in custom-made * Thirteen patients were excluded from MSTS/ISOLS functional evaluation because they died of disease at 4-34 months postoperatively, and another one patient was excluded as a result of hindquarter amputation performed for local recurrence of iliac chondrosarcoma after C-THA; MSTS/ISOLS = Musculoskeletal Tumor Society/International Society of Limb Salvage; F = female; M = male; P-F = proximal femur; MFH = malignant fibrous histiocytoma; GCT = giant cell tumor. * Case series with a mean followup period over 60 months are only listed in Table 2; 15 of 17 patients were primarily treated with an allograft-THA prosthesis composite; à primary malignant bone and soft tissue tumors in 82 patients, solitary metastatic bone tumors in seven, plasmacytoma/myeloma in six, and benign bone tumors in three (fibrous dysplasia two, chondroblastoma one); § the cumulative implant survival rate of C-THA was 67% at 5 and 10 years postoperatively, when patients' death was interpreted as censored to calculate cumulative survival rate.…”
Section: Discussionsupporting
confidence: 85%
“…However, limb-salvage reconstruction of malignant pelvic tumors, especially in the periacetabular region, remains challenging because of the complex anatomy, the difficulty achieving wide surgical margins, and large bone and soft tissue defects after tumor resection. The reconstructive options include resection arthroplasty [7,30,33], iliofemoral or ischiofemoral arthrodesis [9,12], hip transposition method (pseudarthrosis) [3,12,32], free-vascularized fibular graft for pelvic ring reconstruction [29], allograft [2,22,23,26,39], recycled autologous bone graft [16,20], and endoprosthetic replacement [1,4,11,14,18,21,24,25,27,28,34,[36][37][38]. However, no standard reconstructive procedure exists after internal hemipelvectomy for malignant periacetabular tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The 20% infection rate in our series of patients is lower than reported rates in some series [3,4,18,26,27,36,39,41,45,46] and greater or comparable to the experience reported in other studies [1,8,12,13,19,20,29,30,38] ( Table 3). The overall infection rate in many series varied from 10% to 47% after internal hemipelvectomy [1, 3, 4, 8, 10, 12, 13, 18-20, 23, 25-27, 29, 30, 34, 36, 38-41, 45, 46], whereas it ranged from 11% to 38% in patients who had resection and endoprosthetic reconstruction [1,3,12,19,20,26,27,36,45,46]. Abudu et al [3] reported a 26% infection rate in a series of 35 patients undergoing endoprosthetic reconstruction with saddle prostheses.…”
Section: Discussionsupporting
confidence: 79%
“…18 The incidence of primary malignant bone tumor involving the pelvic girdle account for approximately 15% of primary malignant bone tumors. 8 [9][10][11][12] and result in poor implant-related survival (42%). 20 Moreover, any reconstruction methods following a wide excision severely diminish limb function, even if a marginal excision is performed.…”
Section: Discussionmentioning
confidence: 99%
“…8 Periacetabular lesions are the most difficult site to reconstruct because of the complicated anatomical structure and complication rates including deep infection (12-47%), implant dislocation (2-22%), or local recurrence (28-35%) is still high in pelvic lesions. [9][10][11][12][13] In this study, we present a case of high-grade pleomorphic sarcoma involving the right acetabulum, which was successfully treated with curettage and a bone graft after complete remission following caffeine-potentiated chemotherapy. The patient and her parents were informed that her data would be submitted for publication and gave their consent.…”
Section: Introductionmentioning
confidence: 99%